Seasonal evolution of winds, atmospheric tides, and Reynolds stress components in the Southern Hemisphere mesosphere-lower thermosphere in 2019 - Stober, Gunter; Janches, DIego; Matthias, Vivien; Fritts, Dave; Marino, John; Moffat-Griffin, Tracy; Baumgarten, Kathrin; Lee, Wonseok; Murphy, Damian; Ha Kim, Yong; Mitchell, Nicholas; Palo, Scott (Annales Geophysicae, 2021)
In this study we explore the seasonal variability of the mean winds and diurnal and semidiurnal tidal amplitude and phases, as well as the Reynolds stress components during 2019, utilizing meteor radars at six Southern Hemisphere locations ranging from midlatitudes to polar latitudes. These include Tierra del Fuego, King Edward Point on South Georgia island, King Sejong Station, Rothera, Davis, and Mc- Murdo stations. The year 2019 was exceptional in the Southern Hemisphere, due to the occurrence of a rare minor stratospheric warming in September. Our results show a substantial longitudinal and latitudinal seasonal variability of mean winds and tides, pointing towards a wobbling and asymmetric polar vortex. Furthermore, the derived momentum fluxes and wind variances, utilizing a recently developed algorithm, reveal a characteristic seasonal pattern at each location included in this study. The longitudinal and latitudinal variability of vertical flux of zonal and meridional momentum is discussed in the context of polar vortex asymmetry, spatial and temporal variability, and the longitude and latitude dependence of the vertical propagation conditions of gravity waves. The horizontal momentum fluxes exhibit a rather consistent seasonal structure between the stations, while the wind variances indicate a clear seasonal behavior and altitude dependence, showing the largest values at higher altitudes during the hemispheric winter and two variance minima during the equinoxes. Also the hemispheric summer mesopause and the zonal wind reversal can be identified in the wind variances.